Bedform spurs: a result of a trailing helical vortex wake. Issue 1 (3rd July 2017) - Swanson, Travis; Mohrig, David; Kocurek, Gary; Perillo, Mauricio; Venditti, Jeremy
Abstract: The formative conditions for bedform spurs and their roles in bedform dynamics and associated sediment transport are described herein. Bedform spurs are formed by helical vortices that trail from the lee surface of oblique segments of bedform crest lines. Trailing helical vortices quickly route sediment away from the lee surface of their parent bedform, scouring troughs and placing this bed material into the body of the spur. The geometric configuration of bedform spurs to their parent bedform crests is predicted by a cross‐stream Strouhal number. When present, spur‐bearing bedforms and their associated trailing helical wakes exert tremendous control on bedform morphology by routing enhanced sediment transport between adjacent bedforms. Field measurements collected at the North Loup River, Nebraska, and flume experiments described in previous studies demonstrate that this trailing helical vortex‐mediated sediment transport is a mechanism for bedform deformation, interactions and transitions between two‐dimensional and three‐dimensional bedforms.